2006
DOI: 10.1136/jcp.2004.023333
|View full text |Cite
|
Sign up to set email alerts
|

Detection of venous invasion in surgical specimens of colorectal carcinoma: the efficacy of various types of tissue blocks: Table 1

Abstract: Background: Venous invasion (VI) is an important prognosis predictor after colorectal carcinoma (CRC) resection, enabling more accurate staging and influencing postoperative management. Aims: To assess/compare various tissue block types (perpendicular, tangential, across mesentery (AM), from major vessels or lymph nodes (LNs)) for VI detection in CRC. Methods: Fifty two CRCs (51 colectomies, one polypectomy) were studied. Tumours were measured, surface area calculated, and colorectum and bowel wall sites recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…This situation is in some ways analogous to the identification of Bmicrometastases^within lymph nodes draining primary tumors in that the clinical significance of this phenomenon is unclear and may be variable between tumor types-being more significant in malignant melanoma than most carcinomas, for example. 15 This is reflected in the current TNM staging guidelines, which indicate that collections of tumor cells < 0.2 cm across within lymph nodes should be termed Bmicrometastases.^1 6 Within colorectal cancer, studies combining detailed characterization of VI with long-term clinical follow-up will be required to determine the true clinical significance of VI when identified using methods additional to H&E alone. Patients with Dukes C (pTanyN1/2) CRC are now considered for postoperative chemotherapy, whereas this additional treatment is considered for patients with Dukes B * VI was recorded as present if identified using one or more of the four demonstration methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This situation is in some ways analogous to the identification of Bmicrometastases^within lymph nodes draining primary tumors in that the clinical significance of this phenomenon is unclear and may be variable between tumor types-being more significant in malignant melanoma than most carcinomas, for example. 15 This is reflected in the current TNM staging guidelines, which indicate that collections of tumor cells < 0.2 cm across within lymph nodes should be termed Bmicrometastases.^1 6 Within colorectal cancer, studies combining detailed characterization of VI with long-term clinical follow-up will be required to determine the true clinical significance of VI when identified using methods additional to H&E alone. Patients with Dukes C (pTanyN1/2) CRC are now considered for postoperative chemotherapy, whereas this additional treatment is considered for patients with Dukes B * VI was recorded as present if identified using one or more of the four demonstration methods.…”
Section: Discussionmentioning
confidence: 99%
“…The utility of histochemical staining for elastic fibers has been previously demonstrated in CRC. 5,6 Immunohistochemical highlighting of vascular spaces in CRC has previously been performed using factor VIII related antigen and Ulex europeus lectin (both uncommonly used in routine practice today) 8-10 but use of the more modern endothelial markers, such as CD31 and CD34, has been restricted to studies of microvessel density in CRC. 11 Therefore, to our knowledge, our study is the first to use CD31 and CD34 immunohistochemistry to study VI in CRC and to compare these methods to routine hematoxylin staining and elastic fiber immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To minimize the false negative rate, they suggested increasing the number of blocks and slides, using elastic stains and cutting tangential blocks from the perimeter of the tumour, across the mesentery, and from mesenteric vessels. Their results indicate that there is a direct relationship between VI incidence and tumour stage, while inverse relationship was found between VI incidence and tumour differentiation, and the greater mean number of blocks was examined, the higher rates of VI were detected [31]. According to the calculation of Talbot el al., 3.9% of cases with extramural VI would be missed if 5 blocks were taken, while 41.3% would be missed if only 2 blocks were processed [34].…”
Section: The Study Of Utility Of Orcein Staining To Detect VI In Cutamentioning
confidence: 99%
“…Sternberg applied similar system with partially different designations [31]. Most of the studies have found invasion type insignificant [26].…”
Section: The Study Of Utility Of Orcein Staining To Detect VI In Cutamentioning
confidence: 99%